DIGITAL PUBLIC RELATIONS PT BUMI ESTETIKA PERKASA DALAM MEMPRODUKSI KONTEN MITOS ATAU FAKTA PADA MEDIA INSTAGRAM @BUMIESTETIKAPERKASA - Gustrianita; Robbikal Muntaha Meliala; Teguh Tri Susanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Technological advancements have greatly changed communication, especially through digital media. Companies now must use the internet to keep up. Interest in facial care has risen, particularly among women, due to the sharing of skincare and beauty information on social media. However, much of this information is not medically accurate and can confuse the audience about proper treatments. This study looks at how PT Bumi Estetika Perkasa uses “Myth or Fact” content on Instagram to educate and soft sell. It uses qualitative methods and examines 14 pieces of content, with one video performing particularly well. The study finds this approach effectively combines education and marketing. Keywords: CMA, CMC, Digital PR